Anthelmintic Activity of Jatropha (Jatropha curcas linn) Leaf Extract Against Ascaridia galli Worms In Vitro - Jamaluddin, Abdul Wahid; Ainun, Hasri; Ris, Adryani; Amir, Muhammad Nur (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2022)
Ascariasis is an intestinal worm disease caused by Ascaridia galli. This disease can attack the small intestine and cause a decrease in productivity of local breed chickens. Worm infections in chickens can be suppressed by taking precautions and treatment measures such as improving the management of the cage and providing anthelmintic. Medicinal plants that can be used as an alternative anthelmintic are jatropha leaves (Jatropha curcas linn) which contain secondary metabolites such as alkaloids, saponins, tannins, phenolics, flavonoids, triterpenoids, steroids, and glycosides. The study aims to determine the anthelmintic activity of Jatropha leaf extract against Ascaridia galli worms. 75 samples of Ascaridia galli worms were taken from chicken intestines in traditional markets. This research was conducted in vitro with five treatments consisting of one positive control group using Levamisole, one negative control group with 0.5% NaCMC, and three groups of Jatropha leaf extract (JLE) with concentrations of 10%, 15% and 20 %. The results of the study showed that jatropha leaf extract at a concentration of 20% gave a better anthelmintic effect compared with administration of Levamisole as a positive control (+) and jatropha leaf extract had LC50 and LT50 at concentrations of 5.49% and 96.006 minutes.